A retrospective chart review of the features of PTEN hamartoma tumour syndrome in children. Issue 7 (19th May 2017) - Hansen-Kiss, Emily; Beinkampen, Sarah; Adler, Brent; Frazier, Thomas; Prior, Thomas; Erdman, Steven; Eng, Charis; Herman, Gail
Abstract : Objective: It is recognised that 5% – 10 % of children with macrocephaly and autism spectrum disorder (ASD) and/or intellectual disability (ID) have a heterozygous pathogenic mutation in the PTEN tumour suppressor gene that is associated with PTEN hamartoma tumour syndrome. However, the clinical features and course in children with a pathogenic PTEN mutation are unclear and have not been well documented. Study objectives: We undertook a retrospective chart review of children (< 18  years) with pathogenic PTEN mutations to ascertain clinical findings, clinical course and possible outcomes. Results: Clinical and molecular data were collected and analysed for 47 patients with PTEN mutation from 38 eligible families. Macrocephaly (average head circumference of + 5.7  SD) with developmental delay, ID and/or ASD were the most common presenting signs/symptoms (66 %). Clinical features included dermatological findings (66 %), gastrointestinal (GI) symptoms (34 %), ASD diagnosis (50 %), abnormal brain imaging (53 % of those examined) and abnormal thyroid imaging (26 %). Conclusions: This is the largest survey of clinical features in children with PTEN pathogenic mutations to date. It confirms earlier reports of increased rates of neurodevelopmental disorders. Dermatological, GI and thyroid abnormalities are age dependent and may not be present at the time of diagnosis, requiring regular monitoring and medical surveillance. Early paediatric diagnosis is important for institution of medical and developmental surveillance as well as for testing other at- risk family members.